(untitled) (Research, Society and Development, 2021)
Green manuring with spontaneous species from Caatinga biome has become an important strategy in production vegetables. One of the great challenges in tuberous vegetables production is to define an optimized quantity that provides a high productive yield with economic efficiency of production system. The objective of this study was to optimize agronomically and economically the production and its components of tuberous crops of beetroot and radish when manured with different amounts of green manures biomass, Merremia aegyptia and Calotropis procera from Caatinga biome, in two cropping seasons. The experimental design was a randomized complete block with five treatments and five replications. Treatments consisted of green manures amounts (16, 26, 36, 46, 56 t ha-1). The maximum agronomic efficiency of beetroot and radish was obtained with incorporation of 49.87 and 39.43 t ha-1 of M. aegyptia and C. procera, respectively, and the production maximum economic efficiency was reached when 36.14 and 36.48 t ha-1, respectively, of biomass of these green manures were added to the soil. The returns rate obtained in beetroot and radish cultivation using the manures optimized amounts were 1.42 and 1.32 reais obtained for each real invested in the production of these tuberous.